Evaluation of genipin for stabilization of decellularized porcine cartilage. Issue 9 (24th March 2017) - Elder, Steven; Pinheiro, Amanda; Young, Christian; Smith, Preston; Wright, Emily
ABSTRACT: We speculate that an acellular osteochondral xenograft may be a good alternative to allografts for repair of focal articular cartilage lesions. In order to make a xenograft resistant to enzymatic degradation and to prevent a chronic immune response it may be beneficial to stabilize it through crosslinking. The concept is analogous to treatment of porcine bioprosthetic heart valves with glutaraldehyde. The purpose of this study was to evaluate genipin, a natural crosslinking agent with low cytotoxicity, for stabilization of decellularized cartilage. Porcine articular cartilage discs were decellularized in SDS and nucleases and then crosslinked in genipin. The utility of genipin was determined from its effects on degree of crosslinking, mechanical properties, dimensional stability, enzymatic resistance, and in vitro biocompatibility. Degree of crosslinking, compressive moduli, and collagenase resistance varied over a wide range depending on genipin concentration. The equilibrium compressive modulus could be increased from approximately 50% to more than 120% that of native cartilage, and the time to complete degradation by collagenase could be extended from less than 12 h to more than 15 days. Radial shrinkage of approximately 4% was observed at a genipin concentration of 0.1% wt/vol, and cartilage coefficient of friction against glass increased in a concentration‐dependent manner. Autologous chondrocytes displayed little difference in viability or their ability to attach and spread over the surface of genipin‐fixed cartilage compared to non‐crosslinked cartilage during 6 weeks of culture. These results indicate that genipin may be efficacious for stabilization of a decellularized porcine osteochondral xenograft. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1949–1957, 2017.